Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Cohen, Philippa J.; Allison, Edward H.; Andrew, Neil L.; Cinner, Joshua; Evans, Louisa S.; Fabinyi, Michael; Garces, Len R.; Hall, Stephen J.; Hicks, Christina C.; Hughes, Terry P.; Jentoft, Svein; Mills, David J.; et al. (Frontiers in Marine Science, 2019)
The vast developmental opportunities offered by the world’s coasts and oceans have attracted the attention of governments, private enterprises, philanthropic organizations, and international conservation organizations. High-profile dialogue and policy decisions on the future of the ocean are informed largely by economic and ecological research. Key insights from the social sciences raise concerns for food and nutrition security, livelihoods and social justice, but these have yet to gain traction with investors and the policy discourse on transforming ocean governance. The largest group of ocean-users – women and men who service, fish and trade from small-scale fisheries (SSF) – argue that they have been marginalized from the dialogue between international environmental and economic actors that is determining strategies for the future of the ocean. Blue Economy or Blue Growth initiatives see the ocean as the new economic frontier and imply an alignment with social objectives and SSF concerns. Deeper analysis reveals fundamental differences in ideologies, priorities and approaches. We argue that SSF are being subtly and overtly squeezed for geographic, political and economic space by larger scale economic and environmental conservation interests, jeopardizing the substantial benefits SSF provide through the livelihoods of millions of women and men, for the food security of around four billion consumers globally, and in the developing world, as a key source of micro-nutrients and protein for over a billion low-income consumers. Here, we bring insights from social science and SSF to explore how ocean governance might better account for social dimensions of fisheries.